2006
DOI: 10.1128/aem.00511-06
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the hrp Clusters of Xanthomonas oryzae pv. oryzicola That Control the Hypersensitive Response in Nonhost Tobacco and Pathogenicity in Susceptible Host Rice

Abstract: Xanthomonas oryzae pv. oryzicola, the cause of bacterial leaf streak in rice, possesses clusters of hrp genes that determine its ability to elicit a hypersensitive response (HR) in nonhost tobacco and pathogenicity in host rice. A 27-kb region of the genome of X. oryzae pv. oryzicola (RS105) was identified and sequenced, revealing 10 hrp, 9 hrc (hrp conserved), and 8 hpa (hrp-associated) genes and 7 regulatory plant-inducible promoter boxes. While the region from hpa2 to hpaB and the hrpF operon resembled the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
139
0
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(155 citation statements)
references
References 59 publications
4
139
0
12
Order By: Relevance
“…oryzicola (59), and similar gene arrangements are also found in the genomes of X. oryzae pv. oryzae (57), X. campestris pv.…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…oryzicola (59), and similar gene arrangements are also found in the genomes of X. oryzae pv. oryzae (57), X. campestris pv.…”
mentioning
confidence: 73%
“…The expression of hrp genes is induced in planta and in the hrp-inducing medium XOM3 (55) and is controlled by two key regulatory genes, hrpG and hrpX, located outside the hrp gene cluster (59). Commonly, the expression of the hrpA operon and hrpX is activated by an OmpR family member, HrpG (42,54).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, soaking plantlets in suspensions of nonphytopathogenic P. putida ATCC 12633 or media alone also caused wilting. Moreover, we found that after 36 A hallmark of nearly all plant-pathogenic bacteria is the ability to produce a hypersensitive response in tobacco (13,23,79). Tobacco leaves infiltrated with 10 9 cells ml Ϫ1 of B. thailandensis or P. putida did not elicit a hypersensitive response after 7 days, while those infiltrated with the same amount of R. solanacearum developed a hypersensitive response after 2 days.…”
Section: Figmentioning
confidence: 92%
“…Uji hipersensitivitas isolat bakteri terhadap tanaman tembakau dilakukan menurut Zou et al (2006). Koloni hawar daun bakteri hasil isolasi dengan kerapatan ±10 6 sel/ml dalam kultur cair disuntikkan ke tulang daun tanaman tembakau.…”
Section: Metode Penelitianunclassified